Shift of the microbial communities from exposed sandstone rocks to forest soils during pedogenesis. (May 2019) - Liu, Yaping; Lu, Meixi; Zhang, Xiaowen; Sun, Qibiao; Liu, Renlu; Lian, Bin
Abstract: Microbial community structure and their biochemical activities have a significant impact on rock weathering, pedogenesis, and the development and succession of terrestrial biodiversity. In this study, microbial diversity of exposed rock and soils covered by different organisms were analysed through high-throughput sequencing. The results showed that microbial diversity was low in the naked or lichen-covered rock samples, with Cyanobacteria, Chloroflexi, Proteobacteria, and Ascomycota being dominant. The abundance of Ascomycota showed a clear predominance in the lichen-covered surface rock samples (89.30 ± 0.03%). For the soil samples with growing vascular plants, the observed OTUs of bacteria and fungi increased significantly, and the community structure and metabolic types of bacteria became more complex. The bacteria changed gradually from rock weathering pioneers to soil organic decomposers and ecological relation maintainers. In addition, fungi belonging to Basidiomycota, Zygomycota, and Glomeromycota were present in these soil samples, some of them formed mycorrhiza with plant roots. Analysis of the correlation between environmental factors and microbial communities indicates that the total organic carbon (TOC) and content of exchangeable iron exerted the most significant effects on the microbial communities. This study advances our understanding of the microbial community succession process during rock weathering and pedogenesis, and provides a reference for the stabilization and improvement of different soil ecosystems. Highlights: Microbial community from exposed sandstone to forest soil changed obviously. Autotrophic bacteria were pioneers at the early stage of pedogenesis. Microbes became more diverse and form ecological relationships during pedogenesis. TOC and available iron exerted the most effects on the microbial community.